2012
DOI: 10.1094/mpmi-06-11-0154
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Maize Defense Mechanisms Against the Corn Borer Sesamia nonagrioides: A Transcriptome and Biochemical Approach

Abstract: Rodríguez, V.M._2_MPMI after being attacked. These results were confirmed through biochemical analyses showing that the concentration of some cell wall-related compounds significantly changed after plant infestation in a genotype-dependent way. In conclusion, maize plants respond to the attack of the corn borer S. nonagrioides through cell wall fortification, activating genes involved in cell wall organization which finally is reflected in a higher concentration of some cell wall components, especially in resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 52 publications
3
27
1
Order By: Relevance
“…Surprisingly, larvae gained significantly more weight following consumption of LCT compared to control or wounded tissues. Microarray analyses confirmed that numerous defense-related genes were up-regulated in LCT compared to control tissue and shared significant overlap with those reported for the Mediterranean corn borer ( Sesamia nonagrioides ) [52]. Although the expression of many defense-related genes were induced in response to ECB, a correspondingly broad increase proteins was not observed by iTRAQ analysis.…”
Section: Discussionsupporting
confidence: 70%
“…Surprisingly, larvae gained significantly more weight following consumption of LCT compared to control or wounded tissues. Microarray analyses confirmed that numerous defense-related genes were up-regulated in LCT compared to control tissue and shared significant overlap with those reported for the Mediterranean corn borer ( Sesamia nonagrioides ) [52]. Although the expression of many defense-related genes were induced in response to ECB, a correspondingly broad increase proteins was not observed by iTRAQ analysis.…”
Section: Discussionsupporting
confidence: 70%
“…All chitinases belong to family 18 and 19 glycosyl hydrolases, and plant chitinases have been classified into six classes (Hamid et al, 2013). Plant chitinases have been shown to accumulate in response to pathogen attack as well as by herbivory (Kasprzewska, 2003;Rodríguez et al, 2012). When we applied the maize chitinases Pr4 and Endochitinase A, which were both present in fraction B and were attached to the chitin-binding beads, to maize leaves, it induced the expression of the pathogen defense gene marker pr5 (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Studies reporting the induction of chitinases in response to fungal attack in plants also are widely known (Schlumbaum et al, 1986). Maize contains a large chitinase gene family, and some of these are induced by FAW herbivory (Rodríguez et al, 2012). Since Pr4 and Endochitinase A were two of the most abundant proteins with a chitin-binding domain detected in FAW frass (Table III), we measured the transcript abundance of pr4 and endochitinase A in response to caterpillar herbivory.…”
Section: Chitin-binding Proteins In Faw Frass Induced Pathogen Defensmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study demonstrates the powerful role of polysaccharide-polysaccharide cross-linking trough ester-linked DFAs as a natural resistance mechanism of maize against corn borers (damage by stem tunneling was 29% lower in C3H than in C3L) [124]. On the other hand, Rodríguez and coauthors [31] reported that the maize plants respond to the attack of MCB activating genes involved in the cell-wall organization, and moreover, the inbred line PB130 increase twice its DFAs concentration after MCB attack. Current investigations would confirm these motivating findings.…”
Section: Cell Wall Bound Hydroxycinnamatesmentioning
confidence: 99%